2004
DOI: 10.1002/eji.200322663
|View full text |Cite
|
Sign up to set email alerts
|

Signaling assemblies formed in mast cells activated via Fcϵ receptor I dimers

Abstract: Although aggregation of the Fc 4 receptor I (Fc 4 RI) is necessary for Ag-mediated mast cell triggering, the relationship between the extent of the Fc 4 RI aggregation and subsequent biochemical and topographical events is incompletely understood. In this study, we analyzed the activation events induced by Fc 4 RI dimers, elicited by binding of anti-Fc 4 RI mAb to rat basophilic leukemia cells. We found that, in contrast to extensively aggregated Fc 4 RI, receptor dimers (1) induced a less extensive associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 24 publications
5
22
0
Order By: Relevance
“…Although pretreatment with latrunculin did not affect association of several signaling proteins (Lyn, LAT, NTAL and Thy-1) with DRM, it enhanced tyrosine phosphorylation of LAT, NTAL and even Syk, which is not considered to be associated with lipid rafts. It should be noted, however, that Syk could be recruited to lipid rafts through its binding to lipid raftresiding molecules such as Lyn [28] or aggregated FceRI [10,12]. The combined data support the notion that actin cytoskeleton is involved in setting the threshold for activation of mast cells through various pathways.…”
Section: Cross-talk Between Thy-1 and Fcerisupporting
confidence: 59%
See 4 more Smart Citations
“…Although pretreatment with latrunculin did not affect association of several signaling proteins (Lyn, LAT, NTAL and Thy-1) with DRM, it enhanced tyrosine phosphorylation of LAT, NTAL and even Syk, which is not considered to be associated with lipid rafts. It should be noted, however, that Syk could be recruited to lipid rafts through its binding to lipid raftresiding molecules such as Lyn [28] or aggregated FceRI [10,12]. The combined data support the notion that actin cytoskeleton is involved in setting the threshold for activation of mast cells through various pathways.…”
Section: Cross-talk Between Thy-1 and Fcerisupporting
confidence: 59%
“…Based on these results, Wilson and co-authors suggested that the observed FceRI aggregates could represent the true signal transduction organizing units [14]. However, we recently found that mAb-mediated FceRI dimerization induces strong cell activation response in the absence of formation of the large signaling assemblies around FceRI aggregates [12]. Thus, FceRI signal transduction units could be much smaller than previously thought [14,16], and their molecular topography and changes during the course of mast cell activation remain enigmatic.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations